The epidemiological significance of Chagas' disease in womem - Loretta Brabin (Memorias do Instituto Oswaldo Cruz, 1992)
Little is known about the risks associated with Trypanosoma cruzi infection in non-pregnant and pregnant women. From a limited number of studies it appears that in rural areas, parasite rates and rates of serological positivity are similar in both sexes. Abnormal ECG tracings are consistently more frequent in men suggesting that immunity to T. cruzi may be different in females. Complications arising from Chagas' disease in pregnancy are only infrequently reported. Evidence for increased risk of abortion or prematurity is inconclusive except in cases of congenital infection. Most cases of congenital Chagas' disease have been reported from non-endemic areas and there is a suggestion that parasitemic episodes during pregnancy may influence pregnancy outcome. Preliminary evidence indicates that chronic infection can result in in-utero sensitization via passively acquired maternal antibodies. The review concludes that maternal T. cruzi infection carries risks for the child and these warrant systematic research because of their public health significance.